Primary hepatic leiomyosarcoma - A case report with review of literature - Gupta, Sahil (Indian Journal of Case Reports, 2016)
Primary hepatic leiomyosarcoma are very rare tumours with less than 50 cases reported. Due to nonspecific presentations, diagnosis is often delayed until they reach a large size. The rarity of these tumours has precluded our understanding of them and therefore the standard of care has not been well defined. We report a 45-year-old lady who presented with loss of appetite, abdominal distension and bilateral lower limb swelling and hepatomegaly. CT abdomen revealed nodular hepatomegaly with a hypodense lesion on plain scans, heterogenous enhancing lesion on arterial phase and delayed washout on portal venous phase occupying segments VII and VIII and involving right hepatic vein and infiltrating into inferior vena cava (IVC). The pathology report confirmed the diagnosis of leiomyosarcoma. IHC was positive for SMA, vimentin and weakly positive for desmin stain. Due to extensive nature and involvement of IVC, patient was planned for upfront neo-adjuvant chemotherapy (NACT) (Ifosfamide, and doxorubicin with MESNA. The patient has completed 6 cycles NACT and had stable disease. The patient was then switched to oral Pazopanib and is on follow up.